Autism diagnosis as a social process. (February 2022) - Hayes, Jennie; Ford, Tamsin; McCabe, Rose; Russell, Ginny
The diagnosis of autism can be challenging, particularly if an individual coming for assessment is considered to be near the diagnostic threshold. It is important to understand the experiences and challenges of diagnosis from the perspective of clinicians. In this study, 21 in-depth interviews were conducted with clinicians working in specialist autism assessment teams in adult and children's services in England. Interviews were recorded and transcripts were analysed thematically. We identified four themes that represented how clinicians were frequently engaged with juggling their own professional understanding of what autism is with other factors such as the results of standardised tests and the views of patients and carers, in the context of limited resources: institutional pressure, making diagnosis make sense, seeing through an autism lens and just tools. The study illuminates the diagnostic process as a socially situated activity. We suggest that an examination of the benefits and drawbacks of assessment services specialising in autism only, the resources they require to operate effectively, and how they operate in the context of wider health services would be appropriate and timely. Lay abstract: When a child or adult is referred for an autism diagnosis, clinicians from different backgrounds work together to make a diagnostic decision. A few studies have asked clinicians in interview how they feel about diagnosis and what the challenges are. We interviewed clinicians in child and adult assessment services in England, and from different professional backgrounds, about the challenges of autism diagnosis and the factors that might influence the assessment process. We found that there were a number of challenges in autism diagnosis, especially when someone coming for diagnosis was considered to be near the diagnostic threshold. Clinicians told us that making a diagnosis was like creating a 'narrative': looking at many different factors that told a story about a person, rather than just looking at the results of diagnostic tests. Clinicians do not always agree with the results of those tests and have to use their specialist clinical judgement to make decisions. Clinicians were concerned about the amount of time people have to wait for an autism assessment, and the resulting pressure on the assessment process. The findings of this work can help us to understand how diagnosis happens and consider ways in which it can be improved for adults, children and families coming for assessment, as well as clinicians.